(untitled) (Teología, 2019)
The author aims to give an overall view of the Logos as found in this commentary on John. The Logos is really God, because he is eternal and because he differs substantially from every creature (created from nothing), all ofwhich are created by the Father through him. He is the only begotten, the Son by nature. Above all, because only the Father is God by antonomasia. The Logos is God (without the article) because he lives contemplating the Father. He is the intermediary in the making creatures divine. The Logoscreatures share in him; they are the image of the image. The Father is the prototype and the Logos is the archetype. The Father is greater than the Logos because he is the origin. The Spirit, the third in the hypostasis, is not the Son, because he comes by means of the Son. The Son, eternally begotten, is born from the Father as the will to understand, as the splendor of light. Origen clearly distinguishes the hypostasis but he had not sufficient vocabulary to express its unity, as Nicaea had. The vision of Origen of the Trinity is more dynamic. We must rise up to the God- Logos, who was from the beginning directed to God. So, as children, we will contemplate the Father. Such is the imposing vision of the coming from the Father and returning to him. With regard to the Incarnation Origen got some things right and some wrong.